Numerical studies on internal flow in pipelines of an aquaculture vessel and flow control using a special branch pipe - Huang, Wenyun; Zha, Ruosi (Frontiers in Marine Science, 2023)
Regarded as the world’s largest smart-aquaculture vessel so far, Guoxin No. 1, has achieved remarkable success in aim to develop large-scale cruising aquaculture platforms. Guoxin No. 1 is 816 feet long with 15 fish farming tanks, which has a tank capacity of up to 900,000 square feet. It is of great practical interest to study the pipe flow rate distribution involving oxygen and novel flow control schemes for internal flows of aquacultural facilities connecting fish farming tanks. In this paper, three-dimensional numerical investigations on internal flow in a T-type pipeline and its flow control are carried out. A single pump is designed to convert water to two separate farming tanks through a pipeline system, which is composed of one main inlet pipe and two outlet pipes with the same diameter as that of the inlet pipe. A horizontal arrangement of the pipes, in which the flow rate of an outlet pipe must be half of the inflow rate, is firstly studied for validation. To guarantee a balanced oxygen supply, equilibrium outflow rates can be achieved as a consequence of using a branch with a smaller diameter installed on the main inlet pipe. A couple of flow rates and three pipe angles were then investigated to assess the change of the outflow rates. 3-D unsteady RANS solvers were employed to simulate the incompressible viscous flow and the pipe walls were assumed as rigid bodies. Based on the simulations, a flow control scheme was proposed including to optimize the central included angle between the main inlet pipe and the small branch pipe, and the inflow rate of the branch pipe in order to balance the outflow rates. The results show that the central included angle has a significant influence on the flow field and flow rate of the two outlet pipes. If the angle was fixed, it can be indicated that adjusting the flow rate of the branch inlet can be an efficient method to unify the flow rate of the outlet pipes and improve the water exchange among fish farming tanks.